HOP: Hardware makes Obfuscation Practical - Nayak, Kartik; Fletcher, Christopher W.; Ren, Ling; Chandran, Nishanth; Lokam, Satya; Shi, Elaine; Goyal, Vipul (Network and Distributed System Security Symposium 2017, 2017)
Program obfuscation is a central primitive in cryptography, and has important real-world applications in protecting software from IP theft. However, well known results from the cryptographic literature have shown that software only virtual black box (VBB) obfuscation of general programs is impossible. In this paper we propose HOP, a system (with matching theoretic analysis) that achieves simulation-secure obfuscation for RAM programs, using secure hardware to circumvent previous impossibility results. To the best of our knowledge, HOP is the first implementation of a provably secure VBB obfuscation scheme in any model under any assumptions. HOP trusts only a hardware single-chip processor. We present a theoretical model for our complete hardware design and prove its security in the UC framework. Our goal is both provable security and practicality. To this end, our theoretic analysis accounts for all optimizations used in our practical design, including the use of a hardware Oblivious RAM (ORAM), hardware scratchpad memories, instruction scheduling techniques and context switching. We then detail a prototype hardware implementation of HOP. The complete design requires 72% of the area of a V7485t Field Programmable Gate Array (FPGA) chip. Evaluated on a variety of benchmarks, HOP achieves an overhead of 8X to 76X relative to an insecure system. Compared to all prior (not implemented) work that strives to achieve obfuscation, HOP improves performance by more than three orders of magnitude. We view this as an important step towards deploying obfuscation technology in practice.